APPLICATION OF GENETIC ALGORITHM TO OPTIMIZE WATER DISCHARGE AT BATU TEGI DAM - Aprizal, Aprizal; Rahmat, Rahmat (University Muhammadiyah Jakarta, 2025)
Water is the largest natural resource in Indonesia and it is easy to use in its utilization. Water that can be utilized directly from the river or by collecting rainwater in a tando pond orreservoir and then flowing it to turn a turbine. To utilize the available water resources, thegovernment always builds and maintains its facilities and infrastructure, including bybuilding dams. Unpredictable rain intensity, especially in the Lampung area, can cause a lackof optimal water release. If the release of water is not optimal, then the need for water willnot be obtained optimally, but the presence of water in the reservoir cannot always be fulfilledwhen it is needed. The Batu Tegi Dam is an important dam for the needs of the surroundingwatershed and Tanggamus. When building a system, optimization is an importantcomponent. System design can reduce processing time, among others through optimization.Mathematical functions are usually used to describe optimization problems. The process ofmaximizing or minimizing the objective function while taking into account the existingconstraints is known as optimization. This calculation uses the Microsoft Excel 2021application. By analyzing the optimal release discharge, as well as displaying the optimaldischarge value in 2022 using the Genetic Algorithm method. This method is the expertise offlexibility and accuracy when maximizing complex systems. The results of this study obtainoptimal discharge before and after using the Genetic Algorithm (GA) method with a timeseries of 2018 to 2022, making a discharge discharge curve in 2022. Keywords: Genetic Algorithm, Dam, Release Optimization